The Cult of Pushkin in the Context of Popular Literature Over the Course of a Century (1837–1937): Kalavszky Zsófia: A totális Puskin. Populáris műfajok a Puskin-kultuszban, 1837–1937 [Zsófia Kalavszky: The total Pushkin. Popular genres in the Pushkin cult, 1837–1937]. Budapest, Reciti, 2024, 398 p. ISBN: 978-963-672-015-5 - Regéczi, Ildikó (Slavica, 2026)
The publication of Zsófia Kalavszky’s monograph is a landmark event in the field of Russian studies in Hungary. In this thorough scholarly work, Kalavszky explores the nature of the Pushkin cult, offering important findings into the century following the Russian poet’s death and tracing his evolution into an iconic figure. Rather than focusing on commemorative texts by literary giants, she ventures into the realm of popular literature to track the shifts in the myth surrounding Pushkin, reflecting changes occurring in specific historical eras and within the receiving audience. The monograph conveys in-depth expertise in a way that makes it an engaging read for a broad audience.